Intervensi Penerapan Terapi Bermain dengan POP-IT untuk Mengurangi Kecemasan pada An. N dengan Bronkopneumonia di Ruang Aster RSUD Prof. Dr. Margono Soekarjo Purwokerto - Melinda Agustin; Noor Yunida Triana (Pusat Riset dan Inovasi Nasional, 2026)
Bronchopneumonia is one of the lower respiratory tract infections commonly found in children and may cause impaired gas exchange and psychological problems such as anxiety during hospitalization. Toddlers often experience fear of medical procedures, especially nebulizer therapy due to the sound and vapor produced by the device. Untreated anxiety may lead to uncooperative behavior and interfere with treatment. One non-pharmacological intervention to reduce anxiety in children is play therapy using POP-IT. This study aimed to determine the implementation of POP-IT play therapy in reducing anxiety among children with bronchopneumonia during nebulizer administration. This study used a descriptive case study design with a nursing care approach on a 2.5- year-old child diagnosed with bronchopneumonia in Aster Ward at RSUD Prof. Dr. Margono Soekarjo Purwokerto. The intervention was conducted for three days by providing POP-IT play therapy before and during nebulizer therapy. Evaluation was carried out using behavioral observation and the Visual Analog Scale (VAS). The results showed a decrease in anxiety level from a score of 7 (severe anxiety) on the first day to a score of 3 (mild anxiety) on the third day. The patient became more cooperative, no longer cried during procedures, appeared calmer, and was able to interact with nurses. Vital signs also improved with decreased body temperature, pulse rate, and respiratory rate. In conclusion, POP-IT play therapy is effective in reducing anxiety in children with bronchopneumonia during nebulizer administration.